Mummies in the Closet: A Cultural Reading of Women Murderers (KULT_online, 2011)
In her book Women, Murder and Femininity: Gender Representations of Women Who Kill (2010) Lizzie Seal develops a typology of five discourses of womanhood as they appear in cultural and legal narratives surrounding unusual murders committed by women: discourses of the witch, the masculine woman, the damaged personality, the muse and/or mastermind, and the respectable woman. Seal’s close reading of original archival material of 1950s/60s British murder cases as well as of portrayals of notorious women killers sheds light on the disciplinary nature of the discourses with regard to gender, and offers insights into symbolic meanings of femininity in 1950s/60s British culture.